2020
DOI: 10.3390/polym12010218
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ageing in Water Solution Containing Iron Sulfate on the Mechanical Properties of Epoxy Adhesives

Abstract: This study investigates the effect of operating factors such as seasoning in water solution containing iron (II) sulfate—FeSO4 (5 different water solution variants were tested) on the mechanical properties of an adhesive compound made of epoxy resin and amine curing agent, in a ratio of 100 g resin to 12 g curing agent. Strength tests of cured adhesive compound samples were performed on the Zwick/Roell Z150 testing machine in compliance with the EN ISO 604 standard. During the tests, compression modulus, compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The main advantages of epoxies over other thermosetting resins reside in their low shrinkage displayed during curing, in the possibility to process (i.e., "cure") the resins in different environmental As previously outlined, the epoxies are severely affected by the environmental conditions that characterize their curing process as well as their whole service life. In particular, if it is expected that an epoxy will be subjected to an aggressive environment during its service life, or it is merely exposed outdoors, it is necessary to analyse the effect of the specific service environment on its characteristics, even at different exposure times [14,16,17,20,38,39]. The presence of humidity or liquid water is considered one of the most detrimental environment that can be encountered by structural adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of epoxies over other thermosetting resins reside in their low shrinkage displayed during curing, in the possibility to process (i.e., "cure") the resins in different environmental As previously outlined, the epoxies are severely affected by the environmental conditions that characterize their curing process as well as their whole service life. In particular, if it is expected that an epoxy will be subjected to an aggressive environment during its service life, or it is merely exposed outdoors, it is necessary to analyse the effect of the specific service environment on its characteristics, even at different exposure times [14,16,17,20,38,39]. The presence of humidity or liquid water is considered one of the most detrimental environment that can be encountered by structural adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…The curing agent is an amine curing agent (triethylenetetramine curing agent, Z-1 trade name, CIECH Resins, Nowa Sarzyna, Poland). The properties of the used epoxy resin and curing agent were presented in [ 33 , 36 ]. Strength parameters of the used epoxy resin with the addition of the triethylenetetramine curing agent after being cured for seven days at ambient temperature are presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Works dealing with the analysis of the degradation process of epoxy compositions in various aqueous environments have previously been published [ 19 , 21 , 24 , 27 , 28 , 29 , 30 , 31 , 32 ]. In the work by Rudawska and Brunella [ 33 ], the effect of operating factors such as seasoning in water solution, containing iron sulfate, and the time of seasoning was investigated. Based on the obtained results, it has been found that too high an iron sulfate content in water has a negative effect on the selected mechanical properties of the epoxy compound.…”
Section: Introductionmentioning
confidence: 99%
“…Bending strength (MPa) 80-100 Compressive strength (MPa) 70-90 Shear strength of joint cured for 16 h at 20-25 • C, 6 h at 80 ± 2 • C (MPa), not lower than 7.84 Shear strength of joint cured for 7 days at 20-25 • C (MPa), not lower than 5.86 The selected physicochemical properties of Epidian 53 epoxy resin were presented in [6].…”
Section: Properties Valuementioning
confidence: 99%
“…In liquid form, they can be used for joining elements made of different materials. When subjected to curing, however, these materials form solid, resistant structures with low specific weight, which show different properties in various environments [5][6][7][8][9], including water [10][11][12][13], moisture [14][15][16], humid [17][18][19] or hydrothermal conditions [20].…”
Section: Introductionmentioning
confidence: 99%